PENAMBAHAN PERASAN JERUK NIPIS DAN JAHE SERTA KOMBINASINYA TERHADAP KUALITAS KIMIA SE’I DAGING KAMBING (The Addition of Lime, Ginger juice and their Combination on the Chemical Quality of Se’i Goat) - Irene Mbowa; Bastari Sabtu; Gemini E.M Malelak; Hendrikus Umbu Padu (Universitas Nusa Cendana, 2023)
Meat is a food product that is easily spoiled if it is not processed/preserved immediately after being harvested. One way to process meat is by smoking it. The purpose of this study was to know the chemical quality of goat se’i using lime juice, ginger juice and a combination of lime and ginger juice. A Completely Randomized Design (CRD) 4×4, were allotted in this experiment. The four treatments were P₀ = Control, P₁ = Addition of 15% ginger juice, P₂ = Addition of 3% lime juice, P₃ = Addition of 15% ginger juice + 3% lime juice. The results of this study stated that ttreatments were significant difference (P<0.05) on antioxidant activity and the best was in a combination of 3% lime + 15% ginger (P3). The treatments were not significant difference (P>0.05) on fat content, protein content, fat oxidation (TBA) . It was concluded that taddition of 3% lime juice or 15% ginger and their combination in se’i goat increased the antioxidant activityand the best is in 3% lime + 15% ginger (P3).